2008
DOI: 10.1002/eji.200737832
|View full text |Cite
|
Sign up to set email alerts
|

Tapasin shapes immunodominance hierarchies according to the kinetic stability of peptide – MHC class I complexes

Abstract: Peptide loading of MHC class I molecules involves multiple cofactors including tapasin. We showed previously in vitro that tapasin edits the peptide repertoire by favoring the binding of peptides with slow dissociation rates. Here, using tapasin-deficient mice and a DNA vaccine that primes directly, we confirm that tapasin establishes hierarchical responses in vivo according to peptide-MHC stability. In contrast, this hierarchy is lost when the peptides are cross-presented via an alternative DNA vaccine. By re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…Another parameter that might characterize peptide HLA-I complexes involving SYFPEITHI peptides is peptide-HLA-I stability, which has been suggested to be a better indicator of peptide immunogenicity than affinity (19,20). Thus, we speculated whether Tpn 1-87 would affect the stability of peptide-HLA-I complexes and whether the Tpn 1-87 facilitation would depend upon the peptide-HLA-I stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another parameter that might characterize peptide HLA-I complexes involving SYFPEITHI peptides is peptide-HLA-I stability, which has been suggested to be a better indicator of peptide immunogenicity than affinity (19,20). Thus, we speculated whether Tpn 1-87 would affect the stability of peptide-HLA-I complexes and whether the Tpn 1-87 facilitation would depend upon the peptide-HLA-I stability.…”
Section: Resultsmentioning
confidence: 99%
“…However, findings from several different experimental systems suggest that tapasin selectively associates with peptide-receptive MHC-I molecules: 1) a direct interaction between recombinant tapasin and peptideempty HLA-A*02:01 was demonstrated, and this interaction was sensitive to and could be disrupted by MHC-I binding peptide (29); 2) when using purified microsomes, the addition of high affinity peptides efficiently released MHC-I from tapasin (30); 3) in the absence of suitable peptides, i.e. in the TAPdeficient T2 cells, MHC-I molecules accumulate bound to tapasin for over 40 min before dissociation (6, 30); 4) another study using recombinant tapasin and HLA-B*08:01 showed that tapasin acts directly on HLA-B*08:01 as a chaperone increasing the number of peptide-receptive MHC-I molecules (31); and 5) finally, tapasin was demonstrated to increase the average affinity of the peptides to MHC-I presented at the cell surface (32) and to increase the stability of peptide-MHC-I complexes (20). Hence, inside the PLC, tapasin is thought to retain and keep MHC-I molecules in a peptide-receptive state until trimming of suboptimal peptides or replacement with optimal peptides allows the release of stable peptide-MHC-I complexes from the PLC (33).…”
Section: Discussionmentioning
confidence: 99%
“…Still, if no higher affinity peptide is present, many peptides can become trapped in the binding groove and presented at the surface because their encounter complexes can convert to the stable form. Intriguingly, it was recently shown that only in the presence, but not in the absence, of tapasin, peptides are presented according to their kinetic stability [45]. This suggests that the sequence features of the peptide that bring about the CP Ã -CP conversion are not identical to those that determine high-affinity equilibrium binding.…”
mentioning
confidence: 99%
“…In the absence of Tapasin, MHC I molecules can be loaded with fast off-rate suboptimal peptides that can be lost before reaching the cell surface. 12,13 The low surface expression of MHC I molecules resulted in impaired positive and negative thymic T-cell selection, resulting in a reduction of CD8 þ T-cell number in the thymus and periphery, and reduced antigen presentation to T cells, resulting in poor in vivo CTL response to influenza virus. 14,15 HBcAg 18-27 epitope (HBcAg [18][19][20][21][22][23][24][25][26][27] ) is a widely accepted as a CTL epitope to stimulate CTL response to hepatitis B core antigen (HBcAg).…”
mentioning
confidence: 99%